Tradisi Lisan Aceh dalam Intat Linto (Antar Pengantin): Pantun Seumapa - Raiyana Putri Kana; Rosmawaty Harahap; Elly Prihasti Wuriyani (Medan Resource Center, 2022)
Seumapa rhymes is an oral tradition in Aceh whose contents are related to marital problems. In other words, this rhyme is a rhyme delivered by the linto baro and dara baro parties at the wedding procession. This pantun is still an Acehnese tradition, although the rules are not as strict as before. The rhyme is started by the singer from the side of the linto baro as a guest, namely greeting the dara baro as the host that the linto baro group has arrived. Furthermore, answered by the virgin baro. And so on until the linto baro is allowed to enter the arena of the wedding party or to the house to eat the next meal. This study aims to reveal in depth the contents of the